Analisis Tingkat Kesehatan Pada Aspek Jati Diri Koperasi Pada Koperasi Syariah Hayatussunah Masjid Jami Mungsolkanas Chiampelas-Bandung - Nurjamil, Nurjamil; Nurkhalifah, Eva (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2025)
This study aims to determine the health level of the Hidayatussunnah Sharia Cooperative at the Jami Munsolkanas Chimapelas-Bandung Mosque. To analyze the level of health in 2021 which refers to the regulation of the deputy for supervision of the ministry of cooperatives and SMEs No.07/Per/Dep.6/IV/2016 which includes aspects of identity by calculating using two ratios, namely the ratio of gross participation and the ratio of economic participation of members . Which produces calculations from the results of research that has been carried out at the Hidayatussunnah Sharia cooperative Jami Munsolkanas Chimapelas-Bandung Mosque. That this cooperative is included in the category of cooperatives that have low criteria in terms of service to its members and provide sufficient benefits to its members.